Triggering of ¹⁷⁸m²Hf isomer embedded in Ta matrix by 30 keV electrons - Dovbnya, A.N.; Kandybei, S.S.; Kirischuk, V.I.; Ranyuk, Yu.N. (Вопросы атомной науки и техники, 2013)
¹⁷⁸m²Hf isomer triggering was studied using the upgraded experimental setup developed in Kharkiv National University and installed at Kyiv Institute for Nuclear Research. The target presenting a single Ta foil of 300 μm thickness with ¹⁷⁸m²Hf isomeric activity of about 100 Bq was irradiated by 30 keV electron beam. The enhanced counting rates of all the ground-state band transitions were observed. Our data are consistent with an estimate for the triggering effect of (2.9 ± 0.7)% and corresponding triggering cross-section can qualitatively be estimated as σtrig = 4.2 × 10-²⁷ cm². Використовуючи вдосконалену експериментальну установку, розроблену в Харкiвському нацiональному унiверситетi та зiбрану в Київському Iнститутi ядерних дослiджень, вивчався трiггерiнг iзомеру ¹⁷⁸m²Hf В якостi мiшенi використовувалась танталова фольга товщиною 300мкм з ¹⁷⁸m²Hf активнiстю близько 100 Бк, яка опромiнювалась пучком електронiв з енергiєю 30 кеВ. Спостерiгалося збiльшення iнтенсивностi всiх переходiв основної смуги. За отриманими даними ефект трiггерiнга становить (2.9 ± 0.7)% i якiсна оцiнка перетину трiггерiнга вiдповiдає σtrig = 4.2 × 10−²⁷ cm². Используя усовершенствованную экспериментальную установку, разработанную в Харьковском национальном университете и собраную в Киевском Институте ядерных исследований, изучался триггеринг изомера ¹⁷⁸m²Hf. В качестве мишени использовалась танталовая фольга толщиной 300 мкм с ¹⁷⁸m²Hfактивностью около 100 Бк, которая облучалась электронным пучком с энергией 30 кэВ. Наблюдалось увеличение интенсивности всех переходов основной полосы. По полученным данным эффект триггеринга составляет (2.9 ± 0.7)% и качественная оценка сечения триггеринга соответсвует σtrig = 4.2 × 10-²⁷ cм² .